2016
DOI: 10.18632/oncotarget.10750
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of fibroblast growth factor 19 and its receptor associates with progression from fatty liver to hepatocellular carcinoma

Abstract: BackgroundHuman fibroblast growth factor 19 (FGF19), its receptor (FGFR4) and EpCAM play an important role in cell proliferation, differentiation, motility, and overexpression have been linked to hepatocellular carcinoma (HCC). The aim of this study was to evaluate the FGF19 signals responsible for the progression of HCC arising from fatty liver.ResultsFGF19 level was significantly increased in the HCC patients' serum compared to non-HCC controls. The IHC results demonstrated significant increases of protein e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 37 publications
2
47
0
Order By: Relevance
“…FGFR4 is highly expressed in embryonic tissues and overexpressed in many tumor tissues, such as prostate, breast, and pancreatic cancers, and HCC [22-25]. Data show that FGFR4 has an oncogenic role in HCC and chemotherapeutic resistance, and tumor invasion is related to high expression of FGFR4 [26-27]. However, high expression of FGFR4 contributes to apoptosis and better prognoses [25].…”
Section: Discussionmentioning
confidence: 99%
“…FGFR4 is highly expressed in embryonic tissues and overexpressed in many tumor tissues, such as prostate, breast, and pancreatic cancers, and HCC [22-25]. Data show that FGFR4 has an oncogenic role in HCC and chemotherapeutic resistance, and tumor invasion is related to high expression of FGFR4 [26-27]. However, high expression of FGFR4 contributes to apoptosis and better prognoses [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, FGF19 overexpression can be found in a proportion of liver tumors that may exceed 25%, suggesting the existence of additional mechanisms leading to FGF19 upregulation [50][51][52] . Most interestingly, increased hepatocellular FGF19 expression has also been detected in cirrhotic and steatotic livers [30,73] , and it was later described that FGF19 gene amplification was associated with the presence of cirrhosis, which is a preneoplastic condition [53] . Very recently, a study performed in patients with primary biliary cirrhosis showed that hepatic and circulating levels of FGF19 protein were upregulated, with serum FGF19 concentrations correlating with worse liver biochemistry [54] .…”
Section: Defining a Role For The Fgf19-fgfr4/klb Signaling System Inmentioning
confidence: 99%
“…FGF-19 is FXR activation dependently produced in the liver, gallbladder, and the distal small intestine and may despite its short half-life potentially stimulate cell proliferation in the liver and gut [30][31][32][33][34]. Synthetic FGF-19 derivatives may provide a prolonged inhibition of bile acid synthesis via the FGFR4/βklotho signalling axis, which might be beneficial in cholestatic liver disease, but may also have less cell proliferative activity.…”
Section: Ngm282mentioning
confidence: 99%